PERAN GURU SOSIOLOGI DALAM IMPLEMETASI NILAI DISIPLIN PADA SISWA IPS DI SMA ISLAM HARUNIYAH PONTIANAK - Marliyana, Marliyana; Salim, Izhar; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study ed to determine how the role of sociology teachers in the implementation of discipline values in social studies students by directing, guiding, and supervising in Haruniyah Islamic High School. The research approach used is a qualitative approach with a descriptive approach method. Data collection techniques used were observation, interviews, and documentation studies. The analysis in this study was presented descriptively by using informants as many as 9 people consisting of one Sociology teacher and eight Social Sciences students in Haruniyah Islamic High School who were not disciplined. The results of this study indicated that the teacher has played a role in applying the discipline value to social studies students at Haruniyah Islamic High School. The role of the teacher in directing the teacher is to familiarize students to pray before and after the learning process and provide advice to students. The teacher also plays a role in guiding students through providing guidance to students who are not disciplined. Then, the teacher also plays a role in supervising, namely the teacher goes around the class and controls students and gives reprimands and sanctions to students who are not disciplined during the learning process. Keywords: Discipline Values, High School Students, Teacher Role